Developing a dealer customer support center strategy - Hauger, Jarah (Kansas State University, 2014)
As the integration of technology and data rises in production agriculture, John Deere dealers in North America are in a constant quest to differentiate themselves and be more than just an equipment provider. Customers with more technologically advanced products are requiring more support from the dealerships. Each dealership has a unique opportunity to provide unprecedented levels of support and each may do it in a slightly different way. This creates a challenge for Deere & Company in providing resources and support to those dealers in their endeavors. This thesis was requested by Deere & Company (John Deere) to provide the company with information on Dealer Customer Support Centers in North America. In order to provide resources and tools for dealers to be successful, it is necessary to understand what they are currently doing with customer support centers and the barriers to implementing more. An online survey was sent out to the Integrated Solutions Manager at every John Deere Dealer organization in North America. From that survey there were a total of 127 responses. The two most common forms of customer support systems that dealers are using are having Integrated Solutions Staff members take calls directly from customers and having someone within the dealership answer the phone and manually route the call to the right person for support. Data also shows that some of the less common but more technologically advanced methods of support have been implemented more in the past 12 months. Survey analysis indicates that only a small percentage of dealers have a true centralized dedicated support center for customers. This subset of dealers is utilizing several different methods to support customers. The two indicative methods are having a 1-800 number for customers to utilize for support and having a dedicated staff to help customers remotely. Dealers are frequently using several types of tools and resources to help support customers, the most frequently occurring ones include JDLink™ and Data Management Services. Respondents indicated using many other tools to provide value to customers including John Deere Remote Display Access, clinics and optimization sessions and many others. Barriers to implementing more complex forms of customer support are numerous, the biggest of which is the cost of implementation and lack of resources to support a more sophisticated customer support system. With this information, John Deere is better positioned to provide resources and support to our dealer channel facing these challenges.
Keywords: John Deere; Customer support; Precision agriculture; Customer support center